Experimental Study on the Effect of Key Factors on the Soil–Water Characteristic Curves of Fine-Grained Tailings - Cao, Baofeng; Tian, Yakun; Gui, Rong; Liu, Yong (Frontiers in Environmental Science, 2021)
Soil-water characteristic curve(SWCC) is an essential parameter for studying the mechanical properties of unsaturated tailings, which plays an important role in stability assessment and prediction of unsaturated tailings dam. In this paper, the matrix suction was measured indirectly by filter paper-based method to investigate the effects of key factors(gradation, temperature and initial dry density)on the soil-water characteristic curves of fine-grained tailings,and the Van Genuchten model was adopted to obtain the empirical equation of SWCC and to verify the accuracy of experimental results.The results showed that: (1) The Van Genuchten model can well-fit the relationship between matric suction and volumetric moisture content of fine-grained tailings,indicating that experimental data determined by filter paper-based method is accurate and appropriate.(2) At the same volumetric moisture content, the matrix suction increased with decreasing average particle size, and the decrease of temperature will increase the matrix suction and water-holding capacity of fine-grained tailings. The matrix suction of the tailings in summer is 38.3% lower than that in winter under the natural volumetric moisture content(14.0%).(3) when the degree of saturation is less than 60%, the greater the initial dry density, the better the water-holding capacity and matrix suction of fine-grained tailings.